Evaluar la madera plástica como alternativa para la construcción de viviendas rurales en el Guayas - Carrasco Navarrete, Luis Diego (2024)
The pollution caused by plastic waste, which affects both the environment and the housing deficit, is the first point of departure for this project entitled “Evaluar la madera plástica como alternativa para la construcción de viviendas rurales en el Guayas ". It seeks to find an alternative to this situation, in this case the introduction of plastic wood as an environmentally friendly material for the construction of rural housing. In this case, a cost analysis was carried out for the construction of a house made of plastic wood and a house made of traditional materials, with which we were able to observe that the economic viability that has the house made with the eco-friendly material is 25% compared to the house made with traditional materials. This makes it a material that is accessible to all people for its affordable price.